Solidaritas Sosial Melalui Program Corporate Social Responsibility Di Kawasan Pertambangan Aceh Barat - Dialdi Albi; Arfriani Maifizar; Afrizal Tjoetra; Akmal Saputra; Khairan (UNIB Press, 2026)
This study aims to analyze the role of Corporate Social Responsibility (CSR) programs in strengthening social solidarity within communities in the West Aceh mining area. The study was conducted in the area surrounding the PT Mifa Bersaudara coal mine, in villages receiving CSR benefits. The research approach used was descriptive qualitative with an interpretive paradigm, focusing on understanding the social meaning and changes in relationships between residents due to CSR implementation. The research data were collected through interviews, observations, and documentation, then analyzed using a two-way model.The results show that mining activities have changed the socio-economic structure of the community from a homogeneous, agricultural-based society to an industrial society with more functional social relationships. The CSR program plays an important role in bridging emerging social tensions, through economic empowerment activities, skills training, MSME development, and education and health support. The program encourages the emergence of new forms of solidarity based on collaboration and interdependence between social roles, in accordance with Émile Durkheim's concept of organic solidarity. This study concludes that CSR in the West Aceh mining area not only impacts economic welfare but also functions as a mechanism for reconstructing social solidarity in modern society. Sustainability and equitable distribution of CSR benefits are key to maintaining a balance between economic development and social cohesion in mining areas.